PERILAKU KEPEMIMPINAN KEPLA MTs NEGERI 2 MODEL PALEMBANG DALAM PERSPEKTIF TEORI TRANSFORMASIONAL - Feri Aguswijaya (Conciencia, 2016)
The research was a qualitative descriptive, raised the problem How leadership behavior of the principal of State Islamic Junior High School 2 Model of Palembang, and was leadership behavior of the principal of State Islamic Junior High School 2 Model of Palembang, could already be categorized in accordance with the theory of transformational leadership. The data collection was done in three ways, namely: 1) observation; 2) interview; and 3) documentation. The results of this study showed that the leadership behavior of the principal of State Islamic Junior High School 2 Model of Palembang, showed that; had ideals (the idea) great, the belief toward the virtues of the vision and mission that had been set, committed, hard-working type, and had pride of work that always wanted to show the best work. Leadership of principal of State Islamic Junior High School 2 Model of Palembang, showed the behavior as inspiration, motivator, motivator, able to analyze well the strengths, weaknesses, opportunities and challenges faced by the organization he led, a figure that could grow the spirit of team work, were able to arrange a vision and mission and were able to communicate with residents of Islamic Schools, could work as a team, prioritize real work and was able to give solutions to the obstacles that were faced by the organization he led. Leadership behavior of principal of State Islamic Junior High School 2 Model of Palembang, in the perspective of the theory of transformational leadership could also be stated to have conformity with the four factors, namely; Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individual.